Paciente de sexo masculino de 13 años de edad con síndrome nefrótico. - Huacón Medina, Daniel Alberto (2019)
The nephrotic syndrome is used to define various disorders that occur in the kidney usually based on the damage of the tiny blood vessels that contain the kidneys of which help the leakage of toxins and excess water in the blood due to its eminent manifestation of proteinuria present in the mission (urine). The objective of this clinical case is to implement the correct interventions of the nursing staff and to point out the inconveniences that arise with the patient's pathology, and in turn the factors that intervene for their recovery. This clinical study was carried out in a 13-year-old male patient with a medical diagnosis of nephrotic syndrome. Information is obtained from his arrival at the hospital unit about his pathology and since when he has been carrying it, in order to carry out the nursing assessment according to Marjory Gordon's functional patterns and to be able to provide the relevant care according to the needs required by the same. After the interventions performed, improvements have been seen in the patient's health, he is calm and encouraged with the results given so far.